Fermi-edge superfluorescence from a quantum-degenerate electron-hole gas - Kim, Ji-Hee (Nature Publishing Group, 2013)
Nonequilibrium can be a source of order. This rather counterintuitive statement has been proven to be true through a variety of fluctuation-driven, self-organization behaviors exhibited by out-of-equilibrium, many-body systems in nature (physical, chemical, and biological), resulting in the spontaneous appearance of macroscopic coherence. Here, we report on the observation of spontaneous bursts of coherent radiation from a quantum-degenerate gas of nonequilibrium electron-hole pairs in semiconductor quantum wells. Unlike typical spontaneous emission from semiconductors, which occurs at the band edge, the observed emission occurs at the quasi-Fermi edge of the carrier distribution. As the carriers are consumed by recombination, the quasi-Fermi energy goes down toward the band edge, and we observe a continuously red-shifting streak. We interpret this emission as cooperative spontaneous recombination of electron-hole pairs, or superfluorescence (SF), which is enhanced by Coulomb interactions near the Fermi edge. This novel many-body enhancement allows the magnitude of the spontaneously developed macroscopic polarization to exceed the maximum value for ordinary SF, making electron-hole SF even more “super” than atomic SF.